Naoroji Pioneer of Indian Nationalism - Patel, Dinyar (Cambridge Harvard University Press, 2020)
The definitive biography of Dadabhai Naoroji, the nineteenth-century activist who founded the Indian National Congress, was the first British MP of Indian origin, and inspired Gandhi and Nehru. Mahatma Gandhi called Dadabhai Naoroji the (3z(Bfather of the nation,(3y (Ba title that today is reserved for Gandhi himself. Dinyar Patel examines the extraordinary life of this foundational figure in India$1 (Bs modern political history, a devastating critic of British colonialism who served in Parliament as the first-ever Indian MP, forged ties with anti-imperialists around the world, and established Self-Rule or Swaraj as India$1 (Bs objective. Naoroji$1 (Bs political career evolved in three distinct phases. He began as the activist who formulated the (3z(Bdrain of wealth(3y (Btheory, which held the British Raj responsible for India$1 (Bs crippling poverty and devastating famines. His ideas upended conventional wisdom holding that colonialism was beneficial for Indian subjects and put a generation of imperial officials on the defensive. Next, he attempted to influence the British Parliament to Institute political reforms. He immersed himself in British politics, forging links with socialists, Irish home rulers, suffragists, and critics of empire. With these allies, Naoroji clinch his landmark election to the house of Commons in 1892, An event noticed by colonial subjects around the world. Finally, in his Twilight years he grew disillusioned with parliamentary politics and became more radical. He strengthened his ties with British and European socialists, reached out to American anti-imperialists and progressives, and fully enunciated his demand for Swaraj. Only Self-Rule, he declared, could remedy the economic ills brought about by British control in India. Naoroji is the first comprehensive study of the most significant Indian nationalist leader before Gandhi.s
Keywords: Nationalists-India; Naoroji, Dadabhai